Negotiating Islamic Ethics in a Majority-Muslim Society: A Psycho Spiritual Study of Muslim Minority Identity Among Thai Students in Indonesia - Pachaya Pacha-ai (Universitas Muhammadiyah Surabaya, 2025)
This study explores how Muslim students from Thailand belonging to a religious minority in their home country negotiate and reinterpret Islamic ethics (akhlak) when immersed in Indonesia’s majority-Muslim environment. As the sole Thai international student in her program at UIN K.H. Abdurrahman Wahid Pekalongan, the researcher employs autoethnography and in-depth interviews to examine the moral tensions, adaptations, and spiritual reflections that arise from this cultural and religious transition. Grounded in classical Islamic ethical frameworks, particularly Al-Ghazali’s concept of tazkiyat al-nafs (soul purification) and mujahadah al-nafs (inner struggle), the research investigates whether living among a Muslim majority reinforces ethical commitment or leads to moral complacency due to perceived social conformity. Data were collected through personal reflective journals, semi-structured interviews with fellow international Muslim students, and analysis of Islamic ethical texts published between 2015 and 2025. Preliminary findings suggest that minority identity fosters heightened moral awareness, while the homogeneous Islamic environment in Indonesia presents both opportunities for spiritual growth and challenges related to performative religiosity. The study contributes original insights at the intersection of Ilmu Akhlak, psycho-spirituality, and intercultural ethics, offering a nuanced understanding of how context shapes moral agency among Muslim youth. Limitations include the small sample size and reliance on self-reported data; however, the depth of reflective analysis ensures theoretical rigor. This research holds value for educators, counselors, and Islamic scholars seeking to support minority Muslim students in transnational religious settings.